2021
DOI: 10.1021/acs.jpcc.1c04783
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Catalysis in the Hydrogenation and Dehydrogenation of N-Heterocycles for Hydrogen Storage

Abstract: Lack of efficient hydrogen storage method is one of the technical bottlenecks for the implementation of hydrogen energy. Liquid organic hydrogen carriers (LOHCs), especially Nheterocycles, have been considered as potential candidates for both on-board and off-board hydrogen storage owing to their low cost, high gravimetric hydrogen storage capacity, reversibility, and compatibility with the existing infrastructures with minimal modification. LOHCs however encounter severe kinetic barriers in the hydrogen uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…In the area of chemical hydrogen storage and release, many outstanding reviews, perspectives, and accounts on heterogeneous and homogeneous catalytic systems have sprung up, ,, most of which focus on one of the chemical H 2 carriers [formic acid (including formate salts), N -heterocycles, ,, (aromatic) hydrocarbons, , ammonia, , ammonia–borane, or dimethyl ether] or on the individual hydrogen production/​release reactions. Notably, in a large proportion of the previous reports, only one individual reaction, either H 2 storage or H 2 release, is involved or discussed rather than combining those individual reactions to demonstrate the overall concept of chemical H 2 batteries; even the research works are very often entitled to contain the topic of “H 2 storage and release”. Those examples are not considered in this Review.…”
Section: Chemical Hydrogen Storagementioning
confidence: 99%
“…In the area of chemical hydrogen storage and release, many outstanding reviews, perspectives, and accounts on heterogeneous and homogeneous catalytic systems have sprung up, ,, most of which focus on one of the chemical H 2 carriers [formic acid (including formate salts), N -heterocycles, ,, (aromatic) hydrocarbons, , ammonia, , ammonia–borane, or dimethyl ether] or on the individual hydrogen production/​release reactions. Notably, in a large proportion of the previous reports, only one individual reaction, either H 2 storage or H 2 release, is involved or discussed rather than combining those individual reactions to demonstrate the overall concept of chemical H 2 batteries; even the research works are very often entitled to contain the topic of “H 2 storage and release”. Those examples are not considered in this Review.…”
Section: Chemical Hydrogen Storagementioning
confidence: 99%
“…[6] Moreover, catalyst stability and recycling issues can further complicate the design of these processes. [7] Heterogeneous dehydrogenation catalysts that operate at temperatures higher than 120 °C and contain precious metal supported nanoparticles have been developed to address this issue at yields exceeding 95 %. In one example, Deraedt et al have shown that the dendrimer-stabilized nanoparticles of palladium (Pd), platinum (Pt), and rhodium (Rh) supported on SBA-15 silica can drive the dehydrogenation of 1,2,3,4-tetrahydroquinoline (THQ) to completion in 23 h at 130 °C.…”
Section: Introductionmentioning
confidence: 99%
“…N‐substituted heterocycles have lower dehydrogenation energy barrier when compared to cycloalkanes, and thus provide a low‐energy opportunity for H 2 release [6] . Moreover, catalyst stability and recycling issues can further complicate the design of these processes [7] . Heterogeneous dehydrogenation catalysts that operate at temperatures higher than 120 °C and contain precious metal supported nanoparticles have been developed to address this issue at yields exceeding 95 %.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Several other triazines show wide-spread pharmacological activities as antiprotozoal, anticancer, antimalarial, antiviral, antimicrobial, antitumor, antituberculosis, anti HSV-1, and anti-HIV. [15][16][17] The literature is flooded with several reports of multicomponent triazine synthesis reactions with modifications in oxidants, solvents and starting materials. The development of methods using metal-mediated homogeneous catalysts for synthetic processes related to fine chemicals, such as flavors and pharmaceuticals, has been under attention in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…11–14 Several other triazines show wide-spread pharmacological activities as antiprotozoal, anticancer, antimalarial, antiviral, antimicrobial, antitumor, antituberculosis, anti HSV-1, and anti-HIV. 15–17…”
Section: Introductionmentioning
confidence: 99%